INDUSTRI KREATIF FILM - Srie Mustika Rahayu; Hariyadi Hariyadi; Dalhar Shodiq (Jurnal Sosial Soedirman, 2017)
This article is about how The Lingkar Biru Film Community maintains and develops its existence in Purwokerto. The article aims to provide information and discourse of the phenomena and the patterns of the creative economy in Purwokerto. The article also analyses the efforts by the community to enhance their existence. From the research leading to this article, it can be concluded that effort by LB in developing their existence is maintaining the quality by keep learning, creating and maintaining the quality. By maintaining the quality, one can assess the existence of something so the existence will come as a bonus for those who continue to learn and sharpen the creativity. Besides, LB also tries to avoid conflict among members and to utilize project result to purchase new tools, and the most important are widening the network by raising the link. The internal interaction done by LB in the production and marketing process is very friendly and flexible. The members of the community master in almost all required skills in many areas of production so they can rely on each other. The obstacles found during the process of LB found were more on the technical issues and time because the obstacles to the interaction can be overcome easily since the members have understood the characters and capacities each other. LB tries to keep the quality by always looking for new ideas that they want to create into a masterpiece. This is the most important point in the effort to sharpen the LB creativity in order to raise up the existence of creative economy.